2011
DOI: 10.1073/pnas.1105304109
|View full text |Cite
|
Sign up to set email alerts
|

The c-MYC oncoprotein, the NAMPT enzyme, the SIRT1-inhibitor DBC1, and the SIRT1 deacetylase form a positive feedback loop

Abstract: Silent information regulator 1 (SIRT1) represents an NAD + -dependent deacetylase that inhibits proapoptotic factors including p53. Here we determined whether SIRT1 is downstream of the prototypic c-MYC oncogene, which is activated in the majority of tumors. Elevated expression of c-MYC in human colorectal cancer correlated with increased SIRT1 protein levels. Activation of a conditional c-MYC allele induced increased levels of SIRT1 protein, NAD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
255
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(279 citation statements)
references
References 89 publications
11
255
4
Order By: Relevance
“…In terms of the regulation of estrogen receptor α (ERα) activity, DBC1 and SIRT1 reciprocally interacted with the cell cycle and apoptosis regulator 1 (CCAR1), and modulate its co-activator function to ERα (20). Furthermore, the inactivation of SIRT1 or the introduction of DBC1 promoted c-MYC-induced apoptosis in different cell lines (21). In the present study, we found DBC1 is associated with SIRT1, but that it does not function as a negative regulator of SIRT1 in HCC.…”
Section: Discussionmentioning
confidence: 49%
“…In terms of the regulation of estrogen receptor α (ERα) activity, DBC1 and SIRT1 reciprocally interacted with the cell cycle and apoptosis regulator 1 (CCAR1), and modulate its co-activator function to ERα (20). Furthermore, the inactivation of SIRT1 or the introduction of DBC1 promoted c-MYC-induced apoptosis in different cell lines (21). In the present study, we found DBC1 is associated with SIRT1, but that it does not function as a negative regulator of SIRT1 in HCC.…”
Section: Discussionmentioning
confidence: 49%
“…This striking result adds a new dimension to previous reports on the antitumor activity of tenovin-6 in melanoma and neuroblastoma xenografts (6,12). Supporting its antitumor activity, tenovin-6 also increases degradation of N-myc and c-myc and it increases the levels of FOXO1 acetylation, which are regulated by SirT1 (12)(13)(14).…”
Section: Introductionmentioning
confidence: 47%
“…Moreover, SIRT1 is known to directly regulate c-Myc transcriptional activity in cancer cells, either via the deacetylation of c-Myc or by binding c-Myc and promoting its association with Max. [110][111][112][113] In this regard, it is intriguing that David Sinclair's group now reveals for the first time that the nuclear ability of SIRT1/HIF-1α to inhibit mitochondrial OXPHOS genes functions by decreasing c-Myc-regulated transcription of the key mitochondrial transcription factor A (TFAM). 23 TFAM is required for mitochondrial DNA replication, transcription, and maintenance, and low levels of TFAM appear to lead to first-phase OXPHOS dysfunction triggered by the aging-associated decline of NAD + .…”
Section: Gerometabolites and Oncometabolites Share A Communication LImentioning
confidence: 99%